Multiphase flows with droplets and particles - Crowe, C. T. (Clayton T.) (Boca Raton, FL. : CRC Press, 2012)
'Since the publication of the first edition, there have been significant advances in science and engineering applications of multiphase flows. This second edition reviews these advances while maintaining the same pedagogical approach. The book features a new chapter on the latest developments in carrier-phase turbulence, as well as an extended chapter on numerical modeling that includes new concepts in dense phase flow models. In a chapter on droplet-particle cloud equations, the text now covers the kinetic theory approach, which is commonly used for dense phase flows and incorporated in commercial codes. The exercises have been expanded, and a solution manual is now available'--
'Preface Since the publication of the first edition of Multiphase Flow with Droplets and Particles in 1998 there have been important advances in the science and technology of dispersed phase flows. The intent of the second edition is to include these advances while retaining the organized, pedagogical approach of the first edition. The primary change is the introduction of a new chapter, Chapter 7, on the effect of the dispersed phase particles on the turbulence of the carrier phase. The other chapters have been modified and revised to reflect the new material. Chapter 4 has been updated to include the new information on particle drag and heat transfer. In Chapter 6, a reassessment of the volume-averaged conservation equations has been made with respect to the general applicability of the'two-fluid' concept. Chapter 8, on the equations for the dispersed phase, has been completely rewritten to include the current techniques for modeling dilute and dense flows. Chapter 9, on numerical modeling, has also been rewritten to include DNS and LES as well as volume-averaged equations for the ? - ? and Reynolds stress models. The exercises have been expanded and a solution manual is available to support the use of the book in an instructional environment'--
Rev. ed. of : Multiphase flows with droplets and particles / Clayton Crowe, Martin Sommerfeld, Yutaka Tsuji. 1998.
Includes bibliographical references (p. 461-481) and index.
Keywords: Multiphase flow; Drops; Particles